Perancangan Aplikasi Sistem Informasi Akuntansi Laporan Keuangan Menggunakan Microsoft Access 2016 (Studi Kasus Pada CV. Batara Tour & Travel) - Leony Ridha Imani; Sudjana Sudjana (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research is intended to design an application of the accounting information system of the financial report on the CV. Batara tour & travel using Microsoft access 2016 that can help in managing and recreating financial statements to be more effective and efficient. The design of the application is done using qualitative research methods with case studies and development approaches. The system development method used is the system development life cycle (SDLC). The data used in the manufacture of this application includes primary and secondary data. CV. Batara tour & travel already had an accounting system, but it was still done by hand. As technology progresses, it needs to compile financial statements to determine the financial condition of the company during a particular period, to assist in the business decision making process. By applying computerized accounting information systems for financial statements, it is hoped that it will make it easier for companies to record accounting to make financial statements effectively and efficiently so that companies can make a business decision.